Treatment of thoracolumbar fractures with severe collapse of the anterior and middle columns via balloon-assisted endplate reduction, transpedicular bone grafting and pedicle screw fixation - Hai-qiang Shen; Yun-qin Xu; You-rong Yao; Qi Liu; Lin-ying Zhou; Xiao-jie Chen; Xiao-hong Lu; Xing Zhao; Yong Tang (Journal of Orthopaedic Surgery and Research)
Abstract Purpose Thoracolumbar fractures involving severe collapse of the anterior and middle columns are difficult to reduce via posterior surgery. Therefore, we evaluated the effectiveness of balloon-assisted endplate reduction (BAER), transpedicular bone grafting, and pedicle screw fixation for this type of thoracolumbar fracture. Methods This retrospective study included 87 patients with thoracolumbar fractures involving severe collapse of the anterior and middle columns treated from January 2020 to January 2022. Among them, 37 patients were treated via BAER, transpedicular bone grafting and pedicle screw fixation (Group A). Another 50 patients were treated via preoperative postural reduction combined with posterior pedicle screw fixation (Group B). Routine patient follow-ups were conducted to record the degree of vertebral height maintenance via X-ray and computed tomography (CT) images. The visual analog scale (VAS) score for low back pain and the Oswestry Disability Index (ODI) score were recorded. Results The operative time, blood loss and hospitalization cost were greater in Group A. Significant clinical improvements in the ODI, VAS score, AVBH, MVBH and VWA were achieved in the two groups after surgery. However, the improvements in the AVBH, MVBH and VWA were significantly greater in Group A. During the final follow-up, the VAS and ODI scores in Group A were lower. The spinopelvic parameters at the sagittal position did not significantly differ between the two groups at any time. Conclusions The technique comprising BAER, transpedicular bone grafting, and pedicle screw fixation to treat thoracolumbar fractures with severe collapse of the anterior and middle columns is feasible and provides advantages.